How Does Information About Inequalities Affect Fairness Views and Policy Preferences? Evidence from a Randomized Survey Experiment - Julia Baarck; Mathias Dolls; Lisa Windsteiger (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
This study investigates how information about intergenerational and intragenerational inequality shapes fairness views and policy preferences. Using a large-scale randomized survey experiment with 4,900 respondents in Germany, we test how exposure to information on wealth and age disparities affects (i) perceptions of distributive and intergenerational fairness, and (ii) support for redistributive and future-oriented policies. We find that respondents generally underestimate existing inequalities. Moreover, providing accurate information about the extent of age and wealth disparities has little impact on left-leaning and centrist individuals but elicits a backlash among right-leaning respondents: the information increases their perceived fairness of the status quo and lowers their support for redistributive and future-oriented measures. We attribute these counterintuitive responses to skepticism about the credibility and neutrality of the provided information. Overall, the findings highlight the limits of informational interventions and the potential for factual communication to backfire in politically polarized contexts.
Keywords: D63; D72; J48; D83; D91; H23; 330; fairness views; inequality; policy preferences; survey experiment